A SECURE ZONE BASED CLUSTERING PROTOCOL [ZBCP] FOR MOBILE AD HOC NETWORKS [MANETs] - Gayathri, K. (IJRDO -Journal of Computer Science Engineering, 2016)
Mobile Ad Hoc Networks (MANETs) are described as a collection of multi hop wireless mobile nodes, infrastructure less connectivity and dynamic topology in nature. Designing a secure protocol for Mobile Ad Hoc Network is a challenging task. There are many protocols proposed for secure routing in MANETs In this thesis, we proposed a Zone Based Clustering Protocol [ZBCP] which is a hybrid routing protocol and it is a grouping of both proactive and reactive routing technique in MANETs. The implementation of proposed protocol is based on the clustering technique in Zone Based Routing [ZBR]. Routing Disorder [RD] attack is the major issue in Zone Based Routing [ZBR], the Secure Zone Based Clustering Protocol [ZBCP] can provide a basis for the secure communication between mobile nodes.